DEVELOPMENT OF E-LEARNING TEACHING MATERIALS ON MATRICES BASED ON COGNITIVE LOAD THEORY - Eliana Eliana; Hepsi Nindiasari; Cecep Anwar Hadi Firdos Santosa (FKIP Universitas Muhammadiyah Tangerang, 2021)
Learning will be effective if it can minimize extraneous cognitive load because students' understanding can be improved and stored in long-term memory. The purpose of this study was to determine the development of e-learning teaching materials on matrices based on cognitive load theory that is valid, practical, and effective. The development of this teaching material uses e-LKS (electronic student worksheet) with the help of a liveworksheet and presents example-based learning. This study uses the ADDIE development model. The development steps used are (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. Valid test based on expert judgment shows that e-learning teaching materials on matrices based on cognitive load theory get an average of 4.25 with very valid category so that this teaching material is feasible to use. The practicality test based on the student response questionnaire showed that this teaching material obtained an average of 79.7% with a good category, and the evaluation test showed that this teaching material obtained an average of 78.6% with student completeness in learning so it can be concluded that e-learning teaching materials on matrices based on cognitive load theory can be said to be effective.